Enhanced sludge anaerobic fermentation using microwave pretreatment combined with biosurfactant alkyl polyglycoside. Issue 69 (11th September 2017) - Xiao, Jianwei; Zhao, Liangjun; Shen, Zhe
Abstract : This study investigated the effect of microwave combined with biosurfactant alkyl polyglucose (APG) on sludge anaerobic fermentation in a lab-scale sequencing batch reactor. Abstract : This study investigated the effect of microwave combined with biosurfactant alkyl polyglucose (APG) on sludge anaerobic fermentation in a lab-scale sequencing batch reactor. The experimental results showed that microwave combined with APG has a synergistic effect on sludge solubilization and methanogenesis, and that the optimal dosage of APG was 0.32 g g −1 TSS, the SCFA yield was 351.2 mg COD/volatile suspended solids (VSS), which was 4.7-fold of that in blank. In addition, it was found that microwave pretreatment combined with APG can promote the activity of key enzymes, which was beneficial for the accumulation of SCFA. Microbial community analysis showed that the proportion of Firmicutes greatly improved due to the combination of microwave pretreatment and APG, and the percentage of Firmicutes in the microwave pretreatment & APG reactor was 46.5%, which was 3.1- and 1.1-fold of that in microwave pretreatment and APG reactor alone, respectively.